2018
DOI: 10.1371/journal.pone.0207483
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-phosphorylation of Rb S249 together with CDK5R2/p39 overexpression are associated with impaired cell adhesion and epithelial-to-mesenchymal transition: Implications as a potential lung cancer grading and staging biomarker

Abstract: Prediction of lung cancer metastasis relies on post-resection assessment of tumor histology, which is a severe limitation since only a minority of lung cancer patients are diagnosed with resectable disease. Therefore, characterization of metastasis-predicting biomarkers in pre-resection small biopsy specimens is urgently needed. Here we report a biomarker consisting of the phosphorylation of the retinoblastoma protein (Rb) on serine 249 combined with elevated p39 expression. This biomarker correlates with epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 86 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…GCLC is another tumor suppressor gene that induces synthetic lethality of cancer cells; GCLC deletion is associated with lung cancer development 44 . Moreover, CDK5R2/p39 increased the invasiveness of lung cancer by impairing cell adhesion and promoting epithelial-to-mesenchymal transition 45 . FOXA1 promoted lung cancer development as a suppressor of the tumor immune microenvironment, which facilitates immune evasion of cancer cells 46 .…”
Section: Discussionmentioning
confidence: 99%
“…GCLC is another tumor suppressor gene that induces synthetic lethality of cancer cells; GCLC deletion is associated with lung cancer development 44 . Moreover, CDK5R2/p39 increased the invasiveness of lung cancer by impairing cell adhesion and promoting epithelial-to-mesenchymal transition 45 . FOXA1 promoted lung cancer development as a suppressor of the tumor immune microenvironment, which facilitates immune evasion of cancer cells 46 .…”
Section: Discussionmentioning
confidence: 99%
“…CDK5R2 was involved in positive regulation of cyclin-dependent protein serine/threonine kinase activity, the main ligands were TGF-βs, including TGF-β1~TGF-β5, these members had similar structures and functions that inhibited cell proliferation. It had been demonstrated that decreased expression of CDK5R2 was correlated with poor prognosis of hepatocellular carcinoma (Lu et al, 2011), andPérez-Morales et al(2018) indicated CDK5R2 could be a potential lung cancer grading and staging biomarker, it may have similar effects on PAAD patients. NAP1L2 was a kind of nucleosome assembly protein, regulated cell differentiation and tissue maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry (IHC) was performed on formalin-fixed, paraffin-embedded tumor samples sliced at 4 μm. Samples were stained for CD68 (1:200; MCA1957, BioRad, Hercules, CA, USA), and PDGF-AA (1:250; sc-9974, Santa Cruz Biotechnology, Dallas, TX, USA) following protocol by Pérez-Morales et al, 2018 [ 48 ]. Briefly, slides were heated at 65 °C for 30 min and then deparaffinized using graded xylenes.…”
Section: Methodsmentioning
confidence: 99%